With charity for all : Lincoln and the restoration of the Union - Harris, William C. (William Charles), 1933- (The University Press of Kentucky, 1997)
Although Reconstruction is usually associated with the period after the Civil War, it may be said to have begun when Abraham Lincoln, in his 1861 inaugural address, announced his intention to preserve the Union. The first comprehensive examination of wartime Reconstruction, With Charity for All offers a bold new interpretation of Lincoln's efforts to restore the seceded Southern states to the Union while the Civil War raged. Based in part upon his extensive research in the Library of Congress's Abraham Lincoln Papers, William C. Harris maintains that Lincoln - who preferred the term restoration to reconstruction - held a fundamentally conservative position on the process of reintegrating the South, one that permitted a large measure of self-reconstruction. Reasoning that individuals, not states, had rebelled, Lincoln sought to replace those who had usurped constitutional authority with white Southern Unionists who would restore legitimate governments in their states. Beginning with the elevation of Lincoln's policies, describes what happened when military and civil agents tried to implement them, and evaluates the president's successes and failures in attempting a quick restoration of the Southern states to their "proper practical relation with the Union."